2021
DOI: 10.1177/01634437211037008
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage of COVID-19 state surveillance in Israel: the securitization and militarization of a civil-medical crisis

Abstract: Israel, traditionally known as a nation-in-arms, has been undergoing processes of securitization and militarization from its inception to the present day. While several countries have employed surveillance technologies to tackle the spread of coronavirus, Israel was the only country in the world to authorize its internal security agency to track citizens’ cellphones to deal with this civil-medical crisis. Employing a reflexive thematic analysis to news media outlets, this study examined coverage of Israel Secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This militarism, which is part and parcel of the Israeli mentality, provides survival as a justification in relation to many topics discussed in Israeli society ( 36 ), for example, self-sacrifice, sanctification of death, and the encouragement of childbirth ( 37 ). During the COVID-19 period, such language appeared in the media, where it was used to justify and intensify the collection of medical data, epidemiological investigation, and surveillance of citizens ( 38 ). In daily life, militaristic metaphors were used also in coverage of the existential threat to Israel's health system, especially by individuals within the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This militarism, which is part and parcel of the Israeli mentality, provides survival as a justification in relation to many topics discussed in Israeli society ( 36 ), for example, self-sacrifice, sanctification of death, and the encouragement of childbirth ( 37 ). During the COVID-19 period, such language appeared in the media, where it was used to justify and intensify the collection of medical data, epidemiological investigation, and surveillance of citizens ( 38 ). In daily life, militaristic metaphors were used also in coverage of the existential threat to Israel's health system, especially by individuals within the system.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of militaristic terms by clinicians helped create a sense of cohesion in the face of an external threat and merged with the media expressions of “winning the war” and the “battle against the virus” ( 36 ). However, this use of metaphors also served to generate feelings of stress and distress with the aim of pressuring decision makers to adopt policies that would benefit the health system ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…to a division in society according to the principle of attitude to vaccination (Kirziuk 2021; Voronov 2021). As a result, there were many debates about how important social networks are in the dissemination of information, whether the state can interfere in the free functioning of the media to relieve tension and establish calm, whether freedom of speech is still more important, how social networks should be managed in a medical crisis and what the tasks of the state are (Sharifee;Nematollahzadeh & Labafi 2019;Marciano & Yadlin 2021). Panic is faster than official messages from government officials and doctors.…”
Section: Panic and Anxietymentioning
confidence: 99%
“…This article focuses on the personal and international scapes only, because the national scape has been given sufficient scholarly attention since the outbreak of COVID-19. For example, recent studies have shown that media coverage of COVID-19 commonly employs war metaphors and vocabularies (e.g., Marciano & Yadlin, 2021 ; Semino, 2021 ). Such observations from COVID-19 studies correspond with what we already know about the centrality of national security motifs in media coverage of surveillance (see Marciano, 2019 ).…”
Section: Introductionmentioning
confidence: 99%